Simulated Research on the Industry DC Power Supply System Schemes Based on Inductive Filtering Transformer - NING Zhihao; ZHOU Guandong; WANG Can; ZUO Jian (Kongzhi Yu Xinxi Jishu)
In order to solve the problems of conventional 12-pulse and multiple rectifier system such as lower efficiency and larger noise of transformer, it presented a novel rectifier transformer based on inductive filtering technology, introduced normal uncontrollable and controllable DC power supply schemes with such transformers and comparatively analyzed harmonic suppression, harmonic magnetic flux suppression, power factor’s promotion, loss decreasing and energy-saving of the system in Matlab simulations. Simulation results show that the new industry DC power supply units have the advantages of good harmonic suppression and energy- saving, and the advantages of the controllable DC power supply scheme are more distinct in terms of structure and energy- saving.